Differences in local and systemic inflammatory markers in patients with obstructive airways disease - Tilemann, Lisa (Prim Care Respir J, 2011)
BACKGROUND: Asthma and chronic obstructive pulmonary disease (COPD) are characterised by airway and systemic inflammation, but little is known about differences and similarities in inflammatory markers in patients with obstructive airways disease. METHODS: In 210 adult patients presenting to their general practitioners with symptoms suggestive of obstructive airways disease, lung function, fractional exhaled nitric oxide (FE(NO)), blood eosinophils, and serum levels of high-sensitivity C-reactive protein (hs-CRP) and IgE were measured. RESULTS: hs-CRP levels were increased in COPD patients (p=0.009), whereas FE(NO), IgE, and eosinophils were increased in patients with asthma (p=0.009, p=0.041, and p=0.009, respectively). In the ROC analysis, hs-CRP had the largest area under the curve (AUC=0.651; 95% confidence interval (CI) 0.552 to 0.749), with a specifity of 83% and a sensitivity of 42% for the diagnosis of COPD. FE(NO) was the most accurate marker in the diagnosis of asthma (AUC=0.618; 95% CI 0.529 to 0.706). Serum hs-CRP levels correlated with the number of smoking pack-years (r=0.218, p=0.001) and inversely with lung function parameters. CONCLUSIONS: Levels of serum hs-CRP, IgE, blood eosinophils, and FE(NO) identify distinct aspects of local and systemic inflammation in patients with obstructive airways disease. This might help to differentiate between asthma and COPD in primary care patients when spirometry is not available.